Ichu valorization by pleurotus spp. cultivation and potential of the residual substrate as a biofertilizer - Solórzano Acosta, Richard Andi (2025)
The high-Andean grass Jarava ichu (Poaceae) plays a vital role in water regulation and aquifer recharge. However, its limited use is often linked to forest fires, highlighting the need for sustainable alternatives. Therefore, this study aims to explore the valorization of ichu as a substrate for the cultivation of Pleurotus spp. (P. citrinopileatus, P. djamor, and P. ostreatus) and to evaluate the potential of the residual substrate as a biofertilizer, offering an ecological alternative to grassland burning in the Peruvian Andes. Samples of ichu from the district of Tomás (Lima, Peru) were used as culture substrate, analyzing productivity indicators such as crop cycle (CC), biological efficiency (BE), and production rate (PR), together with the nutritional profile of the fungi and the chemical properties of the residual substrate. The results showed an average biological efficiency of 19.8%, with no significant differences (p > 0.05) in CC, BE, or PR among the species, confirming the viability of ichu as a substrate. The fungi presented a high protein content (24.1–30.41% on a dry basis), highlighting its nutritional value. In addition, the residual substrate exhibited elevated levels of phosphorus (795.9–1296.9 ppm) and potassium (253.1–291.3 ppm) compared to raw ichu (0.11–7.77 ppm for both nutrients). Germination tests on radish seeds showed rates between 80% and 100%, without inhibition, supporting its potential as a biofertilizer. This study demonstrates the double potential of ichu as a substrate for the sustainable production of edible mushrooms of high nutritional value and as a source of biofertilizers.